Persistent infection by Staphylococcus epidermidis in endodontic flare-up: A case report - Gonçalves, Simone Helena Ferreira [UNESP]; De Vasconcelos, Rafaela Andrade; Das Neves Cavalcanti, Bruno; Camargo, Carlos Henrique Ribeiro (My University, 2016)
Endodontic flare-ups are challenging situations and may result from selective growth of specific bacterial species; microbial cultures and antibiograms should be used to allow faster, successful management of refractory lesions. A 47-year-old man reported pain on percussion after uncomplicated retreatment of the maxillary left canine for prosthetic purposes. In the following days, pain dramatically increased, leading to removal of the filling and use of intracanal medication. After many unsuccessful attempts to resolve the problem, a microbial culture of the root canal detected the presence of Staphylococcus epidermidis. An antibiogram determined the best drug combination to control this infection: Tetracycline (oxytetracycline hydrochloride, 500 mg orally) plus third-generation cephalosporin (ceftriaxone, 1 g intramuscularly). Once the infection was controlled, the root canal was obturated. There was a reduction in the area of radiolucency, and the patient reported no pain at a 2-year follow-up.
Keywords: Antibiotics; Biofilm; Endodontic flare-up; Retreatment; Staphylococcus epidermidis